FINE ART AND ITS DEVELOPMENT TENDENCIES (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article provides information about the emergence of visual art, its development, examples of painting in the ancient world, and the first examples of visual art in Uzbekistan.